SAT0179 Serum rituximab levels and efficiency of B-cell depletion: Differences between patients with systemic lupus erythematosus and rheumatoid arthritis. (23rd January 2014) - Reddy, V.; Croca, S.; Gerona, D.; Ortega, I.D.L.T.; Isenberg, D.; Leandro, M.; Cambridge, G.
Abstract : Background: Variability in rituximab-induced B cell depletion (BCD) occurs in a significant number of patients with Systemic Lupus Erythematosus (SLE) and to a lesser extent in patients with Rheumatoid Arthritis (RA). A failure to adequately deplete (CD19+ B cells <5/μl) probably underlies poor clinical response in many patients with SLE. In this prospective study, we investigated whether the levels of rituximab influence the degree of peripheral BCD. Objectives: To determine the serum levels of rituximab at 1 and 3 months post-rituximab in SLE and RA in conjunction with the measurement of absolute number of peripheral CD19+ B cells. Methods: A total of 16 patients with SLE were included and 23 with RA. All patients were treated with rituximab (2 x 1g doses given 2 week apart). Rituximab levels at 1 and 3 months post treatment were measured with a capture ELISA using sera diluted at a concentration of 1/40, 000. CD19 counts were determined by flow cytometry. Adequate depletion was defined as CD19+ count below 5cells/ml. Data were compared using the Mann Whitney U test for non-parametric data and the Spearman Rank for correlation. Results: At 1 month, 6 of 15 (40%) patients with SLE and 6 of 23 (26%) patients with RA had CD19 counts >5 cells/ml. The median CD19 count in these patients was 0.02cells/μl and 0.008cells/μl for SLE and RA, respectively. The levels of rituximab were significantly lower in SLE when compared with RA, at both 1 and 3 months after rituximab treatment. The median rituximab level at 1 month for SLE was 43.07μg/ml (range 0-777) and for RA, 391.9μg/ml (range 1.3-2500) (p=0.0008). The median rituximab level at 3 months was 0μg/ml (range 0-54) for SLE and 2.6μg/ml (range 0-1153) for RA (p=0.008). Amongst patients who had depleted well, rituximab levels were significantly lower in patients with SLE when compared with patients who have RA at 1 month (p=0.003) and also at 3 months (p=0.008). No such difference was found in patients who did not deplete well. Six patients with SLE had lupus nephritis (LN) and the presence of LN did not influence the levels of rituximab or the degree of BCD, in this small group of patients. The levels of rituximab correlated inversely with the absolute numbers of CD19+ B cells in patients with RA at 1 month (r 2 =0.69) and in patients with SLE at 3 months (r 2 =0.51). Conclusions: Our data indicated that patients with SLE had markedly (>9 fold at 1 month) lower serum levels than RA patients at both 1 and 3 months. However, a higher proportion of patients with SLE depleted less well with significantly higher residual CD19+ B cells due to factors involved in the clearance of rituximab such as impaired recycling through FcRn, internalisation and destruction by target B cells. Disclosure of Interest: None Declared